2018
DOI: 10.3390/ijerph15091957
|View full text |Cite
|
Sign up to set email alerts
|

In the Heart of the Amazon: Noncommunicable Diseases and Apolipoprotein E4 Genotype in the Riverine Population

Abstract: The Amazon River basin is the largest tropical forest in the world. Most of the Amazon belongs to Brazil, a developing country that currently faces huge challenges related to the consolidation of its universal healthcare system. Noncommunicable diseases (NCDs) are the leading cause of death in Brazil, accounting for 74% of all deaths, and NCDs are probably underestimated in Amazonian population because of their geographical isolation and the precariousness of riverine communities. Important risk factors, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…In this work, the NC revealed that more than 60% of the participants were at risk for possible metabolic complications in both regions, and that the prevalence of men with a risk related to these complications is higher than that of women ( Figure 3 ). These data would explain the previous findings of the significantly higher median blood pressure and hypertension prevalence in men compared to women [ 10 ]. However, additional studies are needed to better understand the higher prevalence of women at risk showed by the other anthropometric parameters.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In this work, the NC revealed that more than 60% of the participants were at risk for possible metabolic complications in both regions, and that the prevalence of men with a risk related to these complications is higher than that of women ( Figure 3 ). These data would explain the previous findings of the significantly higher median blood pressure and hypertension prevalence in men compared to women [ 10 ]. However, additional studies are needed to better understand the higher prevalence of women at risk showed by the other anthropometric parameters.…”
Section: Discussionsupporting
confidence: 70%
“…A higher proportion of women participated in our study, especially in the Tapajós region (71% of all participants) ( Table 2 ). This is frequent in epidemiological studies of Amazonian populations, and it has been attributed to a higher concern about health [ 10 ], with women self-reporting more symptoms of illness [ 33 ]. Our data about occupation, showing a high frequency of housekeepers in both regions ( Figure 2 ), confirm previous descriptions of Amazonian populations observing that women were responsible for all domestic work, in addition to child care [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the characteristics of these populations (precarious health care system, low purchasing power, geographical isolation, etc.) [2,5,7,8,63,72], similar to those of other vulnerable populations in the world. Thus, the use of endemic plants is a more realistic alternative for these populations to protect themselves against MeHg-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 56%